The Association of Socioeconomic and Nutritional with Risk of Tuberculosis in DM Type 2 Patient - Pantaria Noor Fitri; Muhammad Atoillah Isfandiari (Universitas Airlangga, 2017)
Diabetes mellitus (DM) is a disease caused by the ineffective use of insulin. East Java is a province with the top 10 prevalence of DM in Indonesia. DM patients have a higher risk of developing tuberculosis (TB). This study aims to determine the socioeconomic relationship and nutritional status with the risk of TB in patients with type 2 DM in Tambaksari Sub-district, Surabaya. This research is a retrospective quantitative research with case-control study design matching age and gender. The sample in this study was calculated by matching the formula found in 38 patients with DM for TB and 38 DM for controls. This research was conducted at a Public health center (PHC) located in the Tambaksari sub-district area in January - December 2016. The sampling technique using simple random sampling. The results showed that the majority of people with DM with TB aged between 56-65 years (50%), male (60.5%), came from the Javanese (73.7%), had the last education below the senior high school level (76.3%), not working (51.3%), earning below the Regional Minimum Wage (UMK) (97.4%), and included in the thin nutritional status category or Body Mass Index (BMI) <18.5 (60.5%). Employment status (p = 0.022; OR = 3.297; 95% CI = 1,288-8,440), income level (p = 0.009; OR = 13,214; 95% CI = 1,597-109,370), and nutritional status (p = 0,000; OR = 17,889; 95% CI = 4,653-68,772) associated with the risk of TB in type 2 DM patients. The conclusion of this study is socioeconomic factors that are not working and income <UMK, and the nutritional status of BMI <18.5 is related to the incidence of TB in DM Patients type 2, so it is necessary to socialize dietary settings in patients with type 2 diabetes. It is necessary to screen TB in patients with type 2 diabetes who have a nutritional status of BMI <18.5.